Effects of arm cranking exercise on muscle oxygenation between active and inactive muscles in people with spinal cord injury. (2nd November 2021) - Horiuchi, Masahiro
Abstract : Objective: We investigated the effects of the incremental arm-cranking exercise (ACE) on tissue oxygen saturation (StO2 ) between active and inactive muscles, and the relationship between peak oxygen uptake (VO2peak ) and changes in the StO2 in inactive muscles. Design: Observational study. Setting: Community-based supervised intervention. Participants: The participants were individuals with motor and sensory complete spinal cord injury (complete SCI; n = 8) and motor complete but sensory incomplete SCI (incomplete SCI; n = 8), and able-bodied (AB) individuals (n = 8) matched for age, height, and body mass index. Intervention: The ACE was performed at a rate increasing by 10 watts min −1 until exhaustion. Outcome Measures: VO2peak, heart rate (HR), and StO2 . Results: While VO2peak was similar among the groups, peak HR was significantly higher in both SCI groups than in the AB (P < 0.05). In active muscles (biceps brachii), no differences in the StO2 were observed among the groups (P > 0.05). In inactive muscles (vastus lateralis), the StO2 in the AB and the incomplete SCI began to decrease at approximately 40% of the peak work rate; however, they remained unchanged in the complete SCI. The reductions in StO2 in the AB were significantly greater than in the incomplete SCI. Conclusions: These results suggest that sympathetic vasoconstriction occurred in the incomplete SCI and AB, although it did not occur in the complete SCI, probably due to a reduction in sympathetic nerve activity. Sympathetic vasoconstriction in inactive muscles may not contribute to an individual's VO2peak regardless of their group.